Pengaruh Realisasi Pajak dan Retribusi Terhadap Rencana Anggaran Pendapatan Asli Daerah dalam pelaksanaan Otonomi Daerah - Eka Sari Ningsih (Universitas Malahayati, 2014)
Abstract. The Purpose of This study was to determine the effect of the realization of the tax levy and realization of the plan of the originalincome budget in the implementation of regional autonomy in Tulang Bawang district in the year 2006-2013 either partially or simultaneously. The techniques of data collection in this study is the,interview, and documentation.In this study the authors use qualitative and quantitative data analysis. In general, tis results of this reaserach are as significant effect on the realization of tax revenue budget plan area is in the implementation, realization levy significant effect on the original income budget plan in the implementation of regional autonomy,realization and realization levy taxes jointly significant effect on the original income budget plan in the implementation of regional autonomy in Tulang Bawang in 2006-2013